2022
DOI: 10.1002/hep.32315
|View full text |Cite
|
Sign up to set email alerts
|

Placebo effect on progression and regression in NASH: Evidence from a meta‐analysis

Abstract: Background and Aims The evaluation of the natural history of NASH has been limited. Currently, liver biopsy remains the gold standard in the assessment of NASH. Placebo‐controlled trials represent a controlled environment with paired biopsies for the evaluation of NASH. This meta‐analysis thus seeks to quantify the change severity of NASH over time, with patients on placebo arms from randomized controlled trials (RCTs) to examine the natural history of NASH. Methods A search was conducted to include NASH RCTs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 101 publications
1
34
0
Order By: Relevance
“…Our study has several limitations. First, due to its retrospective nature and cross-sectional design, this study could have been subject to selection bias and may only present snapshots of NASH that could be resolved and/or progressed over time ( 29 ). Second, the availability of the XL probe in only one institute has limited further analysis regarding the probe type.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has several limitations. First, due to its retrospective nature and cross-sectional design, this study could have been subject to selection bias and may only present snapshots of NASH that could be resolved and/or progressed over time ( 29 ). Second, the availability of the XL probe in only one institute has limited further analysis regarding the probe type.…”
Section: Discussionmentioning
confidence: 99%
“…All rights reserved. pharmacological interventions 218 , which is an important consideration for the assessment of histologic response in placebo-treated patients in designing future phase 2 and 3 trials.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…11 Liver fibrosis, which was once thought to be irreversible, can be reversed if the underlying trigger resolves. 11 Therefore, because NAFLD and NASH are metabolic diseases, changes in lifestyle will mainly dictate the course of the disease. 11 The Middle East has one of the highest prevalence of NAFLD, which was found to be around 32%.…”
Section: Introductionmentioning
confidence: 99%
“…11 Therefore, because NAFLD and NASH are metabolic diseases, changes in lifestyle will mainly dictate the course of the disease. 11 The Middle East has one of the highest prevalence of NAFLD, which was found to be around 32%. 12 One study found a prevalence rate of about 58.5% which is the upper limit in the 95% CI (%), but this may be due to the high number of overweight and patients with obesity recruited for the sample population (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation